Efficacy of suspension exercise training in spinal cord injury: a systematic review and meta-analysis - Yuntao Li; Minmin Wu; Jiguang Pan; Luwen Zhu (Journal of Orthopaedic Surgery and Research)
Abstract Background Spinal cord injury (SCI) refers to damage sustained by the spinal cord due to direct or indirect external factors, resulting in a variety of motor, sensory, and sphincter dysfunctions. Suspension exercise training (SET), which utilizes neuromuscular activation techniques, has demonstrated lasting benefits for musculoskeletal disorders. The objective of this systematic review and meta-analysis was to rigorously evaluate the safety and effectiveness of SET as an intervention for SCI. Methods The authors conducted a comprehensive search across eight databases to identify all relevant randomized controlled trials (RCTs) on October 20, 2024. Data were extracted, the literature was reviewed, and the methodological quality of the included trials was evaluated. This meta-analysis was performed using Stata version 14.0. Results Thirteen studies involving a total of 883 patients were included. Outcomes: Lower extremity motor function score of the lower extremity motor function score of the American Spinal Injury Association Motor Score (ASIA-LEMS) [weighted mean difference (WMD) = 3.653, 95% confidence interval (CI) (2.351:4.956), P < 0.05], the gait parameters [step length standardized mean difference (SMD) = 0.655,95% CI(0.462:0.849), P < 0.05; step speed SMD = 1.057,95% CI(0.533:1.582), P < 0.05; step frequency SMD = 1.000,95% CI(0.512:1.489), P < 0.05], the Berg Balance Scale score(BBS) [WMD = 6.154,95% CI(5.019:7.289), P < 0.05]. The Modified Barthel Index score (MBI) [WMD = 12.475, 95% CI (5.855:19.094), P < 0.05], and the Modified Ashworth Score(MAS) [WMD=0.756, 95% CI (0.879:0.632), P < 0.05]. Significant improvements were observed in all of the aforementioned outcome indicators, suggesting that SET is likely to be effective in restoring function in patients with SCI. Conclusion This study has demonstrated that SET is likely to improve motor and balance functions, as well as activities of daily living, in patients, while also contributing to a reduction in muscle tone. However, this meta-analysis is limited by the quality of the studies included; therefore, further high-quality research is essential to validate these findings. Systematic review registration PROSPERO; identifier: CRD42024606161. Clinical trial number Not applicable.